Content analysis of food advertising in Turkish television - BEREKET, ABDULLAH; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (WILEY, 2010)
Aim: Television (TV) viewing has been implicated in children's weight gain. We aimed to conduct a comprehensive content analysis of TV food advertising in Turkey. Methods: TV advertisements (ads) in the four most popular national free to air Turkish TV channels, were assessed on two weekdays and two weekend days at four time periods of the day; 0800-1200,1200-1600,1600-2000 and 2000-2400 h for each TV channel (64 h assessed for each TV channel), making a total of 256 h. Each ad was analysed for food and drink content, duration and audiovisual properties. Results: There were 8853 TV ads and 2848 of these were related to food (32.1%). A majority of food ads included high-calorie, high-fat, high-sugar food and drink rather than core/healthy foods (81%). Chocolate and chocolate bars were the most frequently advertised food/drink product, followed by cakes, coffee, tea, candies, gum, fast food, chips, juices/carbonated beverages, margarine and ice-cream formed the highest rate of food products advertised in decreasing order. Thirty per cent of all obesogenic/unhealthy ads targeted childhood by using audiovisual techniques. The proportion of total advertisements which were for food or drink, and the proportion of food advertisements that were for unhealthy foods were both much higher at the weekend (33% vs. 30% and 84% vs. 78%, respectively). The time period between 1600 and 2000 h was the most concentrated time slot (33%) for food advertising. Conclusions: This study provides data for the first time on the high levels of obesogenic food advertising on Turkish TV. This should alarm policy-makers to set limits on food advertising targeted towards children especially in countries like Turkey in which childhood obesity is emerging as an important public health issue.
Keywords: childhood obesity; TV; food advertisements; CHILDHOOD OBESITY; CHILDREN; ADOLESCENTS; OVERWEIGHT; EXTENT